2008
DOI: 10.1105/tpc.108.058529
|View full text |Cite
|
Sign up to set email alerts
|

XopD SUMO Protease Affects Host Transcription, Promotes Pathogen Growth, and Delays Symptom Development inXanthomonas-Infected Tomato Leaves  

Abstract: We demonstrate that XopD, a type III effector from Xanthomonas campestris pathovar vesicatoria (Xcv), suppresses symptom production during the late stages of infection in susceptible tomato (Solanum lycopersicum) leaves. XopD-dependent delay of tissue degeneration correlates with reduced chlorophyll loss, reduced salicylic acid levels, and changes in the mRNA abundance of senescence- and defense-associated genes despite high pathogen titers. Subsequent structure-function analyses led to the discovery that XopD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
186
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(199 citation statements)
references
References 58 publications
8
186
0
1
Order By: Relevance
“…These authors found a widespread suppression of photosynthetic gene expression caused by bacterial effector proteins, indicating that bacterial infection itself influences photosynthesis. In agreement with these results, Mudgett and colleagues (Kim et al, 2008) recently demonstrated that the Xcv effector protein XopD contributes to a delayed development of tissue chlorosis and necrosis. Thus, the effector-mediated effect on photosynthesis was most likely responsible for the reduced rate of photosynthesis and the expression of corresponding genes observed in both wild-type and transgenic plants in our experiments.…”
Section: Discussionsupporting
confidence: 67%
“…These authors found a widespread suppression of photosynthetic gene expression caused by bacterial effector proteins, indicating that bacterial infection itself influences photosynthesis. In agreement with these results, Mudgett and colleagues (Kim et al, 2008) recently demonstrated that the Xcv effector protein XopD contributes to a delayed development of tissue chlorosis and necrosis. Thus, the effector-mediated effect on photosynthesis was most likely responsible for the reduced rate of photosynthesis and the expression of corresponding genes observed in both wild-type and transgenic plants in our experiments.…”
Section: Discussionsupporting
confidence: 67%
“…Among the ;35 T3Es injected by Xcv into the plant cell, XopD is a modular protein of 760 amino acids that contains (1) a recently identified N-terminal domain of 215 amino acids , (2) a helix-loop-helix domain (HLH), (3) two tandemly repeated ERF-associated amphiphillic repression (EAR) motifs, previously described in plant transcriptional repressors during defense responses (Kazan, 2006), and (4) a C-terminal Cys protease domain with structural similarity to the yeast ubiquitin-like protease 1. Consistent with its protein structure, XopD displays small ubiquitin-like modifier (SUMO) protease (Hotson et al, 2003) and nonspecific DNA binding activities (Kim et al, 2008). In plant cells, XopD is localized in nuclear foci, indicating that host targets are likely nuclear SUMOylated proteins (Hotson et al, 2003;Canonne et al, 2010).…”
Section: Introductionmentioning
confidence: 73%
“…Indeed, the effector protein XopD (Xanthomonas outer protein D) from the tomato (Solanum lycopersicum) pathogen Xanthomonas campestris pv vesicatoria is known to act as a SUMO isopeptidase in planta, and this activity enhances virulence of this pathogen on tomato (Hotson et al, 2003;Kim et al, 2008). Interestingly, XopD appears to have SUMO isopeptidase activity not only toward SUM1 and SUM2 conjugates, but also toward SUM3 conjugates (Colby et al, 2006).…”
Section: Sa-dependent Sum3 Expression Promotes Plant Defense Responsementioning
confidence: 99%